Maternal and perinatal risk in pregnant women over 35 years. - Sanchez, José (2015)
OBJECTIVE: To determine maternal and perinatal risks of pregnant women with advanced age. MATERIALS AND METHODS: births in pregnant women over 35 years old and pregnant women between 19 and 34 years, who formed the control group, from 1 July 1997 and June 30, 1998, in the service studied Archbishop Loayza Hospital obstetrics. RESULTS: association of older pregnant women was found 35 years with a history of chronic bronchial asthma (p <0.05) blood pressure, and complications of placenta previa, elective Caesarean and vaginal tears during this pregnancy. The existing preeclampsia risk associated with the high number of pregnancies and low instruction degree. In the newborn there were early neonatal death and abnormal fetal conditions, transverse and oblique types (p <0.05). CONCLUSION: Older pregnant 35-year association with maternal morbidity and early neonatal mortality.